The Ambience Potential of Coloured Illuminations in Architecture - Stine Louring Nielsen; Carsten Friberg; Ellen Kathrine Hansen (Ambiances)
This article presents the results of a spatial experiment, which investigates the ambience potential of coloured illuminations in architecture. The experiment took place over a period of two weeks, situated in a semi-laboratory setting of a performance art installation. Qualitative methods inspired by sensory ethnography and cultural probes were applied to grasp the fullness and originality of human bodily sensations of coloured illumination by exploring its effects on participants’ perception of body-space interaction. During the days of experimentation participants were interviewed on their bodily sensation in and perception of a space, while being blindfolded and exposed to three different hues of illumination; red, blue and amber. Findings from the experiment showed how participants sensed their bodies and perceived the space around them in a comparatively different manner in relation to the different hues of illumination, independently of being blindfolded or not. By this, the article contributes to spatial innovation in the light of feelings and sensations of ambience, informing a new multisensory understanding of how coloured illumination can affect bodily sensations and perceptions of space, and argues for a general mindful integration of coloured illuminations in architecture as an essential design element.